Structural, Electronic, and Mechanical Properties of 2D Oxidized Diamond (100) Nanofilms. Issue 10 (4th September 2021) - Liu, Yaning; Gong, Mengmeng; Jia, Suna; Gao, Nan; Li, Hongdong
Abstract: In this work, the structural, electronic, and mechanical properties of 2D atomically thick diamond (100) nanofilms with surface oxygen functionalization as a function of layer number ( n ) are investigated by first‐principles calculation. The phonon dispersion curves and ab‐initio molecular dynamics results prove the dynamical and thermal stabilities of the structures at n ≥ 6. The bandgaps of oxidized diamond nanofilms are independent of the layer number, attributed to the main contribution of surface atoms to conductance bands and valence bands near the Fermi energy. The Perdew–Burke–Ernzerhof (PBE) calculations with n from 6 to 22 show that the bandgaps of nanofilms with ether groups on both outmost sides (ether groups on one side and hydrogen functional groups on the other side) are in the region of 1.308–1.838 eV (1.803–1.884 eV). The bandgap values of nanofilms with methoxyacetone groups on both outmost sides (methoxyacetone groups on one side and hydrogen functional groups on the other side) localized in the region of 3.078–3.329 eV (3.135–3.302 eV), and the flat valence bands and conduction bands near the Fermi energy make the easy transition between direct to indirect bandgaps. The calculated elastic constants and acoustic velocities of nanofilms have a significantly parity‐dependent oscillatory phenomenon and increase with increasing film thickness. This work provides new ideas for fabricating 2D diamond‐based nanodevices (i.e., optoelectrical semiconductor devices, micro‐ and nano‐electro‐mechanical systems) with high performances applied in practical fields. Abstract : 2D oxidized diamond (100) nanofilms with layer number of n ≥ 6 are dynamically and thermally stable. The nanofilms with ether group (methoxyacetone group) terminations on both outmost sides are direct (indirect) bandgap semiconductors. The bandgaps and elastic modulus exhibit a parity‐dependent oscillatory phenomenon, relating to the different arrangements of oxidation groups on top and bottom surfaces.